Improving Empathy and Peer Relationships in Adolescents: A Social Cognition Training Approach - Oztop, Fehmi; Bilac, Sanja; Kutuk, Yasin (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to assess the effectiveness of a social cognition training intervention in enhancing empathy and peer relationships among adolescents. By focusing on these critical social and emotional competencies, the research sought to provide empirical evidence supporting the utility of targeted interventions in developmental psychology. Methodology: Employing a randomized controlled trial design, the study involved 30 adolescents aged 13-16 years, randomly assigned to either an experimental group undergoing a structured social cognition training program or a control group receiving no intervention. The program comprised 10 sessions, each lasting 75 minutes, focusing on developing empathy, understanding peer dynamics, and enhancing interpersonal skills. Empathy and peer relationships were measured at baseline, immediately post-intervention, and at a three-month follow-up using standardized tools, with data analysis conducted via SPSS-27 using ANOVA with repeated measurements and Bonferroni post-hoc tests. Findings: Significant improvements were observed in the experimental group, with empathy scores increasing from a pre-test mean of 55.92 (SD = 13.37) to a follow-up mean of 63.95 (SD = 14.44), and peer relationship scores rising from a pre-test mean of 51.71 (SD = 9.66) to a follow-up mean of 58.99 (SD = 10.21). The control group showed negligible changes. Statistical analysis revealed significant effects of time and group, as well as time × group interactions for both empathy (Time × Group: F = 8.30, p < 0.01) and peer relationships (Time × Group: F = 7.33, p < 0.01). Conclusion: The social cognition training intervention significantly enhanced empathy and peer relationships among adolescents, underscoring the potential of such programs to foster essential social skills and emotional understanding. These findings highlight the importance of targeted interventions in supporting adolescent social and emotional development.